Epidemiological study of hydatidosis comparing IgE ELISA test and Western Blot in population of five provinces of Lima region. 2015 - Vildozola Gonzales, Herman (2018)
ntroduction. Diagnosis of some zoonosis in different provinces from the Lima region, motivated on epidemiological investigation. Objective. To determine the prevalence of hydatidosis (echinococosis) in population from Lima region by ELISA IgE test compared with Western Blot. Methods. 560 sera samples were collected from people living in five provinces of Lima region: Canta (n=180), Huaral (n=55), Yauyos (n=133), Cajatambo (n=32) and Huaura (n=160). Antibodies IgE and IgG were detected by ELISA test and Western Blot respectively. Results. 39 samples were positives to ELISA IgE test (seroprevalence 6,96%) and 33 samples were positives to Western Blot IgG test (seroprevalence 5,89%), with light bands of 8 and 16 kDa. Positive samples proceeded from people of provinces of Canta, Yauyos and Huaura. Concordancy were determined between both tests (kappa index = 0,91). 50% (20/39) of positive subjects are from 25 to 60 years old, while less proportion of positives (1/39) were children under 5 years. Conclusions. ELISA IgE test can be used for the detection of positive person to anti Echinococcus spp. antibody, showing very high concordance with Westrn Blot IgG. Could be used in seroepidemiologic studies.